645 views
2 votes
Which of the following equations is equivalent to 3(a + 4) – 5(a – 2) = 22?

8a + 2 = 22
-2a + 2 = 22
8a + 22 = 22
-2a + 22 = 22

User Danil
by
5.3k points

2 Answers

2 votes

Answer:

-2a + 22 = 22

Explanation:

in both a = 0

User Bie
by
5.2k points
5 votes

Answer:

-2a + 22 =22

Explanation:

3(a + 4) -5(a - 2) =22

3a + 12 - 5a + 10 =22

-2a + 22 =22

User MetricMike
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.